The reliability of jointly versus individually conducted competency to stand trial evaluations - Weiss, Rebecca A. (The journal of forensic psychiatry & psychology, 2024)
Competency to stand trial (CST) evaluations ensure that defendants have the capacity to utilize their civic right to participate in their legal defense. The evaluations are referred to as the most commonly requested forensic mental health assessment. However, the need for these evaluations currently outstrips state resources, leading to exorbitant waitlists across the country. Given the extensive waitlists and limited resources relating to these evaluations across the United States, it is important to evaluate potential approaches to expedite the process. New York is one of the several states to require two reports for each initial competency referral. Although New York allows the required examinations to be conducted individually or jointly, and recent recommendations have suggested that clinicians jointly conduct these evaluations when possible, no previous researchers have examined the impact of jointly conducting competency evaluations. This study examined 166 initial CST evaluations for 83 defendants referred for competency treatment that were conducted in New York State in 2015. The joint evaluations produced greater consistency regarding clinical diagnosis and the legal basis for competence but did not impact CST recommendations. The findings support the recommendation to jointly conduct evaluations when possible in states that require two initial evaluations.